Impacto del “atpdea” en los países andinos y en las exportaciones derivadas del proyecto especial chavimochic - Saavedra Ramírez, José Santos (2009)
In this research work the effects on the Andean countries economies (Perú, Colombia, Ecuador and Bolivia) of the subsequent commercial agreements ATPA (1991-2001) and APTDEA (2002-2006) and particularly, on the exports from the Peruvian project, “Proyecto Especial CHAVIMOCHIC” (PECH) has been assessed. It was compared and analyzed the exports from each Andean country as well as those of the agricultural enterprises comprised in the PECH per each exported product and target market. The exports information was accumulated month after month to get the annual information per enterprise and target market. The same procedure was applied to get the information related to the types of exported agricultural products. A 15 years historical series (1995-2008) was achieved. During the period of time 1991-2007 the exports to USA increased from Perú 8.02 times, Ecuador 4.44 times, Colombia 4.06 times and Bolivia 2.49 times turning out that Bolivia was the Andean country that took the least advantage of the agreements, mainly because of agro sanitary problems and scarcity of infrastructure. The agro exports from the PECH increased from US$. 18.82 millions (1995) to US$. 366.49 millions (2008), which meant an increase of 1,847.34, and the generation of 40,000 direct and permanent jobs, among other benefits. In 1995, exports from the PECH represented the 0.34 % of total exports of Perú, and by the year 2008 accounted for the 1.16 %. On the other hand, in 1995, exports from the PECH represented only the 6.83 per cent of the total non-traditional agricultural exports and in 2008 accounted for the 19.17 %, which demonstrates the national importance the PECH, and great impact that has had the ATPDEA in the regional economy. It is concluded that: the commercial agreements ATPA and ATPDEA granted by the United States of America the Andean countries, had an impact very favorable impact on these economies, particularly in Perú by the exports from the PECH, this allowing to predict even greater impacts with the TLC.